1980
DOI: 10.1038/288729a0
|View full text |Cite
|
Sign up to set email alerts
|

Transient haem–globin interactions in photodeligated carboxyhaemoglobin and subunits

Abstract: Although the fixation of ligand to haemoglobin (Hb) is known to be accompanied by changes in protein conformation regulating the oxygen exchange in blood, the mechanism triggering these changes remains undecided. We now report a dynamic approach to this problem using results obtained in a nanosecond laser photolysis study of carboxyhaemoglobin (HbCO) and its isolated subunits. The study is based on our previous observation of a structural evolution of free Hb after photodeligation, manifested through slight va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Because the same spectral change is observed with the same rate and amplitude in the partial photolysis experiment (c) ( Table 1), in which there is both kinetic and spectroscopic evidence that there is no R -* T transition, the associated structural change can be considered as a pure tertiary change. A tertiary change in this time regime has been previously proposed on the basis of transient Raman (14) and single-wavelength absorption studies (15). There is a small change in fractional saturation associated-with relaxation II, suggesting geminate rebinding from a second nonheme binding site in the globin (13).…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Because the same spectral change is observed with the same rate and amplitude in the partial photolysis experiment (c) ( Table 1), in which there is both kinetic and spectroscopic evidence that there is no R -* T transition, the associated structural change can be considered as a pure tertiary change. A tertiary change in this time regime has been previously proposed on the basis of transient Raman (14) and single-wavelength absorption studies (15). There is a small change in fractional saturation associated-with relaxation II, suggesting geminate rebinding from a second nonheme binding site in the globin (13).…”
Section: Resultsmentioning
confidence: 63%
“…This has been interpreted as the rebinding of photodissociated CO that has not yet escaped from the protein into the solvent and is called "geminate" recombination (9-13). At later times, both optical absorption and resonance Raman spectra of the deoxy hemes showed spectral changes in 0.5-5 ,us, which have been interpreted as resulting from tertiary conformational changes of the globin (14,15).No kinetic model has been formulated that relates geminate rebinding to heme stereochemical and globin conformational changes or to the overall thermal ligand dissociation and binding reactions. A major objective of the present study is to make this connection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Time-resolved studies of transients have been limited to optical absorption (11)(12)(13)(14) and resonance Raman spectroscopy (1) (5,6), and infrared absorption spectroscopy (4). Optical absorption studies (4) of lowtemperature metastable species have not revealed differences between deoxy species and photolyzed species owing to incomplete sample photolysis.…”
mentioning
confidence: 99%
“…On this time scale, the heme has relaxed to an Fe z+ high-spin deoxy heme with the iron displaced from the plane of the porphyrin [2,3]. Large scale motions of protein that influence the heme environment are, however, not detectable until many 100's of ns later [3,14,15]. Consequently we have at 10 ns, a deoxy-heme surrounded by the heme environment that 10 ns earlier had been associated with the ligand-saturated porphyrin and is now, by virtue of the induced ligand dissociation, rendered unstable.…”
Section: Methodsmentioning
confidence: 99%